Activities at Thoracic Aortic Research Center, IRCCS Policlinico San Donato. (29th April 2016) - Trimarchi, Santi; Kamman, Arnoud; Lomazzi, Chiara; Segreti, Sara; Cova, Marta; De Vincentiis, Carlo; Frigiola, Alessandro; Menicanti, Lorenzo; Marrocco-Trischitta, Massimiliano M.; Grassi, Viviana; Morganti, Simone; Conti, Michele; et al.
Abstract: The Thoracic Aortic Research Center (TARC) of the IRCCS Policlinico San Donato (PSD) aims to promote research on thoracic aortic diseases, to disclose the scientific knowledge and clinical experience and to develop new scientific paths within the Hospital and the aortic community, in collaboration with other national and international centres. Thoracic Aortic Research Center collaborates with many centres in both Europe (e.g. University of Utrecht, the Netherlands) and the USA (e.g. University of Michigan). This has led to multiple highly regarded publications in respected cardiovascular journals and has led to several PhD programmes resulting in doctorate degrees. Within Italy, in association with the Bioengineering School of the University of Pavia, TARC has founded the "BETA-lab" ( B iomechanics for E ndovascular T reatment of the A orta laboratory), where MDs, Bioengineers, and PhD fellows conduct experimental studies using in vitro/ex vivo models of the physiologic aorta and aortic diseases. Furthermore, a database (iCardiocloud) where the medical imaging of cardiovascular patients from the PSD is structured, for in silico analysis utilizing computational fluid dynamics, and in vitro studies using also 3D printed aortic models. With the role of principal investigator or co-investigator, TARC at PSD has been participating in other several projects, including the International Registry of Acute Aortic Dissection, the International Aortic Arch Surgery Study Group, the European Registry of Endovascular Aortic Repair Complications, the ADSORB and ASSIST trials, and the GREAT registry. International collaborations have included also studies on predictors of aortic growth after dissection with the Yale University and University of Virginia, and on aortic biomarkers with the University of Tokyo.